Landscape of buildings on a rolling hill. All the buildings are white, one is a church and others appear to be barracks, Fort Chippewyan, Alberta. Note on the front reads: ""Ft. Chippewyan Lake Athabasca"". Note on the back reads: ""All Hudson Bay property n (Thomas A. Edge Archives & Special Collections, 1899)
photograph : b&w 16.5 x 5 cm